Mild Photochemical Biofunctionalization of Glass Microchannels - Carvalho, Rui Rijo (Langmuir : the ACS journal of surfaces and colloids, 2017)
The ability to locally modify the inside of microfluidic channels with bioactive molecules is of ever-rising relevance. In this article, we show the direct photochemical coupling of a N-hydroxysuccinimide-terminated ω-alkene onto hydrogen-terminated silicon oxide, and its subsequent functionalization with a catalytically active DNAzyme. To achieve this local attachment of a DNAzyme, we prepared hydrogen-phenyl-terminated glass (H-Φ-glass) by the reaction of glass with H-SiPhCl2. The presence of a radical-stabilizing substituent on the Si atom (i.e., phenyl) enabled the covalent modification of bare glass substrates and of the inside of glass microchannels with a functional organic monolayer that allowed direct reaction with an amine-functionalized biomolecule. In this study, we directly attached an NHS-functionalized alkene to the modified glass surface using light with a wavelength of 328 nm, as evidenced by SCA, G-ATR, XPS, SEM, AFM and fluorescence microscopy. Using these NHS-based active esters on the surface, we performed a direct localized attachment of a horseradish peroxidase (HRP)-mimicking hemin/G-quadruplex (hGQ) DNAzyme complex inside a microfluidic channel. This wall-coated hGQ DNAzyme effectively catalyzed the in-flow oxidation of 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonate) [ABTS] in the presence of hydrogen peroxide. This proof-of-concept of mild biofunctionalization will allow the facile preparation of modified microchannels for myriad biorelevant applications